2015
DOI: 10.1007/s13277-015-3645-2
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA HOTTIP is correlated with progression and prognosis in tongue squamous cell carcinoma

Abstract: Long non-coding RNAs (lncRNAs) have been demonstrated to be a critical role in cancer progression and prognosis. However, little is known about the pathological role of lncRNA HOXA transcript at the distal tip (HOTTIP) in tongue squamous cell carcinoma (TSCC) patients. The aim of this study is to measure the expression of lncRNA HOTTIP in TSCC patients and to explore the clinical significance of the lncRNA HOTTIP. The expression of lncRNA HOTTIP was measured in 86 TSCC tissues and 14 adjacent non-malignant tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
98
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 27 publications
1
98
0
1
Order By: Relevance
“…A flow diagram of the identification and selection of studies is shown in Figure 1. After evaluation, five studies including 460 patients were finally enrolled for further analysis [11, 1416, 21]. The sample size ranged from 52 to 156 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A flow diagram of the identification and selection of studies is shown in Figure 1. After evaluation, five studies including 460 patients were finally enrolled for further analysis [11, 1416, 21]. The sample size ranged from 52 to 156 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The HOXA transcript at the distal tip (HOTTIP) lncRNA, located at the 5′end of the HOXA cluster, was recently functionally characterized [10]. Increased HOTTIP expression has been reported in tongue squamous cell carcinoma [11], lung cancer [12], pancreatic cancer [13], hepatocellular carcinoma [14], osteosarcoma [15], gastric cancer [16], glioma [17] and prostate cancer [18]. In these tumors, HOTTIP may serve as a potential oncogene and be an adverse prognostic factor in patients.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between HOTTIP and the WDR5–mixed lineage leukemia (MLL) complex increases histone H3 lysine 4 trimethylation and activates the expression of multiple 5′-HoxA genes [19]. Recent reports have shown that HOTTIP is associated with cancer metastasis and is a negative prognostic factor in patients with liver and tongue cancer [20, 21]. In addition, HOTTIP expression promotes cancer progression and drug resistance by regulating HoxA13 in pancreatic cancer [22].…”
Section: Introductionmentioning
confidence: 99%
“…An increased expression level of HOTTIP has been observed in various types of tumor (9)(10)(11)(12)(13)(14). Furthermore, the overexpression of HOTTIP has been previously shown to be significantly correlated with poor prognosis (9)(10)(11)(12)(13)(14). Therefore, HOTTIP may be a candidate to serve as a feasible prognostic factor.…”
Section: Introductionmentioning
confidence: 99%